The butterfly transformation and the anamorphosis: A posthumanist reading of gaze in Zhuang Zi and Jacques Lacan - Wang, Quan (Asian philosophy, 2021)
Zhuang Zi has a seminal influence on Jacques Lacan. Seeing enables an observer to penetrate into the nature of the examined thing so that he will have a potential mastery over the observed object. Zhuang Zi encourages us to go beyond human vision and to look at the world from the perspective of the gaze of things. The transition from the eye to the gaze ushers us into a posthumanist world in which multiple species constitute a symbiotic existence. Likewise, Lacan rewrites the triple functions of seeing into scientific discourse as “the moment of seeing,” “the stage of understanding,” and “the moment to conclude.” Unlike Zhuang Zi, Lacan confines the gaze within linguistic signifiers and ascribes its elusiveness to castration. This central lack (castration) could only be observed from an oblique perspective, otherwise it will produce anamorphosis. The trajectory from the eye to the gaze constitutes the Lacanian desire.